BIOGRAFI CHAIDIR:PEJUAMG MEMPERTAHANKAN KEMERDEKAAN DARI KESATUAN BATALYON PAGARUYUNG DI PADANG PARIAMAN (1945-1950) - MARDIYAH, RADHIATUL - (Pendidikan Sejarah, 2014)
This thesis is study about biography that showed background of Chaidir life and the way of Chaidir life in a certain period of time. Chaidir struggle (1945-1950) deserver to be traced as it related to history and has played a role as fighter, regardless big or small the role played. During the writing of this biography about national figures, while local figuress less attention. For that, being the formulation of research problem is as follow: 1) How life Chaidir before joining became a member of the unity Battalyon Pagaruyung? 2) How did the early involvement in the struggle? 3) Chaidir and his role in the Battalyion Pagaruyung? The method used in this writing is the method of history that carried out by several stages.The first stage Hweristics is activities gather or collect data related to all activities of the examined. Source criticism is the second phase of the activities of researching and selecting sources, critically and trace information. The third phase of the interpretation is trushworthy testimony concluded about materialÂ otentitas by doing the interpretation. And the fourth is hitoriography, the author did the writing of findinga in the form of facts, data, resources have been obtained in the form of ascientific paper in accordanse with the norms of research history. Based on the result of this research where obtained prior to joining Chaidir life bacame a member of the unity Battalion Pagaruyung is drived from a simple family and his parents just a farmer and reseller of cake. Early involvement Chaidir in the stuggle starts from BKR, TKR, and TNI.Thats the sruggle that always were and started into the company of SPO (Singa Pasar Oesang) and unity Battalion Pagaruyung. Chaidir and his role in the union Battalion Pagaruyung gets the role as a commander of a squad of seve people.